SA4Ag, a 4-antigen Staphylococcus aureus vaccine, rapidly induces high levels of bacteria-killing antibodies. Issue 8 (22nd February 2017) - Begier, Elizabeth; Seiden, David Joshua; Patton, Michael; Zito, Edward; Severs, Joseph; Cooper, David; Eiden, Joseph; Gruber, William C.; Jansen, Kathrin U.; Anderson, Annaliesa S.; Gurtman, Alejandra
Highlights: A 4-antigen S. aureus vaccine (SA4Ag) targeting multiple virulence factors. A Phase 1 study after finalizing manufacturing process prior to an efficacy study. SA4Ag was well tolerated with a satisfactory safety profile in adults 18–<65 years. SA4Ag rapidly induced high level bacteria-killing antibodies in adults 18–<65 years. The postoperative protective effect of SA4Ag is being assessed in a Phase 2b trial. Abstract: Background: Staphylococcus aureus is a leading cause of healthcare-associated infections. No preventive vaccine is currently licensed. SA4Ag is an investigational 4-antigen S. aureus vaccine, composed of capsular polysaccharide conjugates of serotypes 5 and 8 (CP5 and CP8), recombinant surface protein clumping factor A (r m ClfA), and recombinant manganese transporter protein C (rMntC). This Phase 1 study aimed to confirm the safety and immunogenicity of SA4Ag produced by the final manufacturing process before efficacy study initiation in a surgical population. Methods: Healthy adults (18–<65 years) received one intramuscular SA4Ag injection. Serum functional antibodies were measured at baseline and Day 29 post-vaccination. An opsonophagocytic activity (OPA) assay measured the ability of vaccine-induced antibodies to CP5 and CP8 to kill S. aureus clinical isolates. For MntC and ClfA, antigen-specific immunogenicity was assessed via competitive Luminex® immunoassay (cLIA) and via fibrinogen-binding inhibition (FBI) assay for ClfA only. Reactogenicity and adverse event data were collected. Results: One hundred participants were vaccinated. SA4Ag was well tolerated, with a satisfactory safety profile. On Day 29, OPA geometric mean titers (GMTs) were 45, 738 (CP5, 95% CI: 38, 078–54, 940) and 42, 652 (CP8, 95% CI: 32, 792–55, 477), consistent with 69.2- and 28.9-fold rises in bacteria-killing antibodies, respectively; cLIA GMTs were 2064.4 (MntC, 95% CI: 1518.2–2807.0) and 3081.4 (ClfA, 95% CI: 2422.2–3920.0), consistent with 19.6- and 12.3-fold rises, respectively. Similar to cLIA results, ClfA FBI titers rose 11.0-fold (GMT: 672.2, 95% CI: 499.8–904.2). The vast majority of participants achieved the pre-defined biologically relevant thresholds: CP5: 100%; CP8: 97.9%, ClfA: 87.8%; and MntC 96.9%. Conclusions: SA4Ag was safe, well tolerated, and rapidly induced high levels of bacteria-killing antibodies in healthy adults. A Phase 2B efficacy trial in adults (18–85 years) undergoing elective spinal fusion is ongoing to assess SA4Ag's ability to prevent postoperative invasive surgical site and bloodstream infections caused by S. aureus . Clinicaltrials.gov Identifier :NCT02364596 .